Social Factor Affecting Maternal Mortality at PUMHS, Nawabshah - Rashida Akbar, Farkhana Yasmem, Monika, Shabana Halepoto, Shahnila Karim Bhatti, Raishem Ali (Pakistan Journal of Medical & Health Sciences, 2022)
Objective is to know social factor influencing maternal mortality rate. Study Design: Descriptive cross sectional study. Place and Duration of Study: Department of Gynae & Obstetrics at PUMHS Nawabshah Jan 2021 to 31 December 2021. Methodology: Pregnant women about 60, who came to hospital and unfortunately died due to pregnancy related complications, or who brought dead but died because of pregnancy and abortion, puerperium period at home included in this cross sectional study and know the impact of social factor playing in maternal mortality rate are studied. We studied for about 1year, how women’s social status, education level and financial status and age at marriage, society can change maternal mortality rate. We found that because of the depriving status of women in society that ranges from not involving her at any level of her life’s decision making supplements her to easily fall prey to death during her vulnerable period. Results: Sixty patients died due to pregnancy, abortion and puerperium related complication had mean age of 26.4+-9.3years range (16 -45yrs). The most common preventable cause of maternal mortality in this group is bleeding including both antepartum hemorrhage and post-partum hemorrhage., (n=24,40%), followed by this preeclampsia and eclampsia responsible for (n=18,30%), while obstructed labour accounts about (n=6,10%) and remaining died due to other causes (n=12, 20%) like infection, embolism etc. Factors that exaggerate these deaths include poverty. It was found that (n=30, 50%) women died, only one member earning an unstable job having responsibility of at least 7- 8 family members and monthly income is below 20000 rupees. Another major social factor is education as the majority of women have no formal education (n=36, 60%), so usually they are doing house work without any other paid chores. Many women are married at an early age (n=4, 6%) are teenagers, women didn’t receive antenatal care during their pregnancy (n=40,65%). Many women had 4kids before this pregnancy (n=25, 42%). Conclusion: Social economic status of women and her husband can decrease or increase women chance of death to die during pregnancy, abortion and puerperium time. If these factors are addressed, we will reach the SDG.